Broken engagements the action for breach of promise of marriage and the feminine ideal, 1800-1940 - Lettmaier, Saskia (Oxford : Oxford University Press, 2010)
Lettmaier explores ideals of femininity during the 19th and early 20th centuries by charting responses to broken engagements. Interweaving a history of the legal remedies for a broken promise of marriage with literary accounts from Dickens to Wodehouse, it offers an insight into attitudes to female identity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Breach of promise -- Great Britain -- History -- 19th century; Breach of promise -- Great Britain -- History -- 20th century; Betrothal in literature; Betrothal in motion pictures; Women -- Great Britain -- Social conditions -- 19th century; Women -- Great Britain -- Social conditions -- 20th century